119 TRIGLYCERIDE DISPOSAL AND LIPOPROTEIN LIPASE-MEDIATED FREE FATTY ACID SPILLOVER IN THE SPLANCHNIC BED OF DOGS. Issue 1 (1st January 2007) - Nelson, R. H.; Basu, R.; Edgerton, D.; Roesner, J. C.; Cherrington, A. D.; Miles, J. M.
Abstract : The action of lipoprotein lipase on circulating triglyceride-rich lipoproteins generates fatty acids, some of which "spill over" into the systemic circulation and contribute to the free fatty acid (FFA) pool. The contribution of the splanchnic (SPL) bed to this process is not known. To determine the efficiency of SPL TG storage and the contribution of the SPL bed to whole-body TG disposal, sampling catheters were placed surgically in the femoral artery (A), portal vein (PV), and hepatic vein (HV) of mongrel dogs ( n = 9). Two weeks later, [1- 14 C]oleate and tracer amounts of a lipid emulsion containing [9, 10- 3 H]triolein (to serve as a surrogate for chylomicrons) were infused under postabsorptive conditions. Blood was taken from the three sampling sites every 7.5 minutes × 5 for measurement of TG radioactivity as well as the concentration and specific activity (SA) of plasma oleate. Hepatic artery and PV plasma flow was measured with Transonic flow probes. Oleate concentration was higher in PV than in A (374 ± 36 vs 329 ± 30 μmol/L, p < .02) and lower in HV (305 ± 26 μmol/L) than in PV, p < .001. [ 14 C]Oleate SA was lower in PV than in A (2.10 ± 0.25 vs 2.47 ± 0.30 dpm/nmol, p < .002), but the HV value (2.14 ± 0.23 dpm/nmol) was similar to PV. [ 3 H]Oleate SA was similar in A and PV (7.03 ± 0.58 vs 7.04 ± 0.68 dpm/nmol, p = NS), whereas the value in HV (8.57 ± 0.69 dpm/nmol) was higher than the PV value, p < .005. SPL 3 H TG uptake was 31 ± 6% of systemic TG disappearance. Of the [ 3 H]TG uptake in the SPL bed, 45 ± 9% occurred in nonhepatic tissues and 55 ± 9% in the liver. Fractional spillover of [ 3 H]oleate was 52 ± 10% and 47 ± 9% in nonhepatic SPL tissues and liver, respectively. There was a significant correlation between FFA release from nonhepatic SPL tissues (presumably visceral fat) and nonhepatic fractional spillover ( r = .81, p < .01), consistent with a model in which the rate of intracellular lipolysis influences spillover by determining the direction of net fatty acid flow between the adipocyte and the interstitium. In summary, there is significant spillover of fatty acids derived from circulating TG in both nonhepatic SPL tissues and in the liver in fasting dogs. In nonhepatic SPL tissues, which presumably represent visceral fat, spillover correlates with rates of release of FFA into the portal vein. Considering that the amount of dietary fat that traverses the circulation can be similar to systemic FFA flux, the contribution of spillover of fatty acids from chylomicrons to total portal FFA is of major potential importance. Abnormally high spillover rates in visceral fat could contribute to hepatic insulin resistance by raising postprandial portal venous FFA concentrations.